Plant-recycling of waste tyre rubber into asphalt binder for sustainability: Insight into physicochemical behavior during terminal production - Hongwei Zhang; Xiaoxing Zhang; Haifeng Wang; Xiong Xu (PLoS ONE, 2025)
Crumb Rubber Modified Asphalt (CRMA) offers a vital pathway for global waste tire recycling, with swelling duration critically governing its performance during terminal production. This study examines physicochemical interactions between rubber particles and base asphalt under varied swelling durations. Systematic analyses employing extraction test, FTIR spectroscopy, rotational viscosity measurements, rheological test and Separation test assessed impacts on molecular structure, viscoelastic characteristics, rheological behavior and Storage stability. Results demonstrated that prolonged swelling time minimally influences residual rubber content (Δ ≤ 0.5%) but intensifies thermo-oxidative degradation of rubber particles in oxidation and desulfurization, thereby activating interfacial interactions of rubber particles and bitumen in CRMA binder. Extended swelling time will be able to initially elevate the viscosity through rubber-oil absorption and subsequently reduce the viscosity through dominant degradation, while progressively diminishing temperature susceptibility. Optimized swelling time at 4h can enhance complex modulus and viscoelastic balance through synergistic effects of rubber degradation and interfacial interactions, significantly improving high-temperature rutting resistance of CRMA binder. The softening point difference (SPD) of CRMA4 can be enhanced by 41% to satisfy better storage requirement. The study on the plant-recycling of waste tire rubber in modification of asphalt binder can provide more understandings in the rubberized asphalt binder production through combined analysis of rubber-asphalt compatibility and interfacial strength.